2006
DOI: 10.1002/chin.200623157
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Benzo[h]‐ and Benzo[f]chromeno[2,3‐b]‐pyridine‐5‐ones.

Abstract: chromeno[2,3-b]-pyridine-5-ones. -A variety of new derivatives of the title benzochromenopyridine systems is synthesized. The reaction proceeds via condensation of the corresponding benzochromenecarbonitriles (I) with enamines or o-aminobenzochromenecarbaldehydes (VIII) with active methylene compounds. -(ABDEL-RAHMAN*, A.-R. H.; GIRGES, M. M.; EL-AHL, A.-A. S.; SALLAM, L. M.; Heteroat. Chem. 17 (2006) 1, 2-7; Dep. Chem., Fac. Sci., Mansoura Univ., Mansoura 35516, Egypt; Eng.) -M. Kowall 23-157

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…For example, Kumar et al reported an efficient method for the formation of fused chromeno[2,3- b ]pyridine derivatives under mild conditions via Au(III)-catalyzed aldol reaction (Scheme 1a ); 10 Abdel-Rahman et al reported the synthesis of benzochromeno[2,3- b ]-pyridine derivatives from amino-benzochromone-carbaldehydes and ethyl cyanoacetate in 2006 (Scheme 1b ); 11 Ibrahim synthesized chromeno[2,3- b ]pyridines via the Friedländer reactions of 8-allyl-2-amino-4-oxo-4 H -chromene-3-carboxaldehyde with some carbonyl compounds containing a reactive α-methyl or methylene group in 2010 (Scheme 1c ). 12 Although various synthesis methods for certain substrates have been widely covered in literature, more convenient and effective approaches for the synthesis of chromeno[2,3- b ]pyridine derivatives need to be developed.…”
Section: Table 1 Optimization Of Reaction Conditions ...mentioning
confidence: 99%
“…For example, Kumar et al reported an efficient method for the formation of fused chromeno[2,3- b ]pyridine derivatives under mild conditions via Au(III)-catalyzed aldol reaction (Scheme 1a ); 10 Abdel-Rahman et al reported the synthesis of benzochromeno[2,3- b ]-pyridine derivatives from amino-benzochromone-carbaldehydes and ethyl cyanoacetate in 2006 (Scheme 1b ); 11 Ibrahim synthesized chromeno[2,3- b ]pyridines via the Friedländer reactions of 8-allyl-2-amino-4-oxo-4 H -chromene-3-carboxaldehyde with some carbonyl compounds containing a reactive α-methyl or methylene group in 2010 (Scheme 1c ). 12 Although various synthesis methods for certain substrates have been widely covered in literature, more convenient and effective approaches for the synthesis of chromeno[2,3- b ]pyridine derivatives need to be developed.…”
Section: Table 1 Optimization Of Reaction Conditions ...mentioning
confidence: 99%
“…In the last few years, 1,2,4‐triazole derivatives have attracted the attention of many scientists in agricultural and medicinal fields because of their interesting structural features and biological activities . These derivatives have diverse biological properties, which include anticancer, antitumor, antimicrobial, anti‐inflammatory, antibacterial, antimalarial, antifungal, antiviral, antiproliferative, neuroprotective, pesticidal, herbicidal, antioxidant, anti‐HIV, analgesic, molluscicidal, and anticonvulsant effects …”
Section: Introductionmentioning
confidence: 99%
“…A large number of thiazole-containing derivatives have been reported to have a wide variety of biological activities, such as antibacterial, antifungal, antitubercular, anti-mycobacterial, anticancer and antiviral. [1][2][3][4][5][6] 2-Amino-thiazol acetate esters are present in most organic compounds of interest in biology, pharmacology, and material sciences. 7 Similarly, 1,3,4-oxadiazoles have had appealing attention for the last two decades due to their extensive range of biological activities, such as anti-inflammatory, antifungal, antiparasitic and antimicrobial effects.…”
Section: Introductionmentioning
confidence: 99%